CRM Beyond Technology: Aligning People, Processes, and Platforms for Business Growth - Hemasundara Rao Rada (International Journal of Intelligent Systems and Applications in Engineering, 2025)
However‚ CRM is often treated solely as a software purchase decision․ Research shows that platform capability alone rarely delivers the expected levels of customer‚ operational‚ and financial performance․ In this paper‚ we synthesize the CRM literature to provide a conceptual framework of the interactions between people‚ processes‚ and platforms (4 P) in successful CRM․ We build on the early literature on CRM‚ critical success factors‚ digitalization‚ and AI-empowered CRM and develop a conceptual integrative alignment framework linking the organization of people-capabilities‚ customer-facing processes‚ and enterprise CRM platforms to business value through planned alignment as a mediating mechanism․ Finally‚ we propose a five-level CRM alignment maturity model‚ a layered CRM reference architecture and a CRM critical success factors taxonomy‚ which are based on our survey of the CRM literature․ The contributions of the paper are conceptual․ We take an eclectic set of partial CRM implementation frameworks and consolidate them into a single operational framework for empirical testing‚ and into a concept that practitioners can use as a tool for auditing their CRM implementation․ Relative to prior research on CRM implementation frameworks‚ this article examines the framework’s breadth and depth of integration‚ its boundary condition and its prospect for future empirical investigations․ DOI: https://doi.org/10.17762/ijisae.v13i1s.8493